Efektivitas Mekanisme Penyelesaian Sengketa Pulau Takeshima/Dokdo Melalui Jalur Non-Yuridis - Al Dina Maulidya (Fakultas Hukum Universitas Islam Malang, 2022)
This study aims to determine the effectiveness of the Takeshima/Dokdo Island dispute resolution mechanism between Japan and South Korea through non-juridical channels. The dispute has been started since the Japanese occupation in South Korea, so in this paper the author wants to examine the dispute resolution mechanism that has been carried out by Japan and South Korea in their efforts to resolve the Takeshima/Dokdo Island dispute. This type of research is normative legal research that emphasizes the approach to legislation. The results of this study indicate that the settlement mechanism carried out by Japan and South Korea using non-judicial channels is still not effective. The two countries have negotiated twice, namely in 1998 and 2006. In the same year as the second negotiation, South Korea decided to free itself from the UNCLOS dispute resolution. Then in 2018 Japan established a permanent connection to the island of Takeshima/Dokdo. South Korea's refusal to take the dispute to the International Court of Justice and the failure of negotiations, have left ambiguity over the ownership status of Takeshima/Dokdo islands.